Development of “No Anemia No Stunting” (Si NaNing) Modules and Application in Efforts to Prevent Stunting in Archipelago Regions - Aminin, Fidyah; Kristianto, Jusuf; Rianda, Dewi Puspa; Haryadi, Haryadi; Cintiani, Jeni Cesi (jitek, 2022)
The average prevalence of stunting toddlers in Indonesia from 2005 to 2017 is 36.4%. Incidence of stunting toddlers (short) is a major nutritional problem faced by Indonesia. Stunting cases in the Riau Islands reached 24 percent of the number of babies born in 2018. One of the causes of stunting is the lack of nutrients fulfilment during pregnancy, including anemia in pregnancy. Currently, there is no media module and application for stunting prevention health promotion. The purpose of the study was to determine the effectiveness of the "No Anemia No Stunting" (Si NaNing) application and the Si NaNing Module on stunting prevention. The study was conducted in Tanjungpinang City in May-November 2020. The research design was quasi-experimental with pre-posttest with control group design. The instrument used is a structured questionnaire. Data collection is during the pre test and post test. The population is all pregnant women in Tanjungpinang City. The sample is 30 respondents/pregnant women from Independent Practice of Midwives in Tanjungpinang City. Data analysis used Dependent T Test for the intervention group (application) and Wilcoxon for the control group (module). The results showed that there was a significant difference in knowledge (p value 0.001), attitude (p value 0.001), and motivation (p value 0.001) in pregnant women before and after being given health education using the Si NaNing application. Meanwhile, in the module group, only motivation (p value 0.000) had a significant difference.